(untitled) (Heritage, 2020)
The concept of education reform in Serbia as well as in other countries in transition has faced the challenge of creating a functional, flexible and quality education system in a rapidly changing society. Some of the goals and tasks of the education program important for the subject of Music Culture are to develop awareness of state and national affiliation; nurturing Serbian tradition and culture, as well as the tradition and culture of national minorities; enabling involvement in European and international integration processes. In order for an individual to be formed as socially responsible with a certain attitude towards cultural and national identity, it is necessary to teach the contents of the subject Music Culture – especially those related to our past, its heroes, tradition, folk art, customs, etc. they emphasize knowledge from the social sciences and realize it in such a way that in each processing of the segment of folk tradition its significance, role, time of origin, social circumstances, etc. are emphasized. With this approach, we systematically influence the ubiquity of traditional values in children’s lives. Early exposure of children to musical experiences that include folk art enables the achievement of a higher level of awareness of the social identity of the individual. One of the goals of teaching the subject Music Culture is to nurture folk traditions and creativity and personal identity. Social contents that are closely connected with the acquisition of knowledge from the tradition of the people are in the subject World around us and Nature and society. "The main purpose of studying the integrated subject World Around Us / Nature and Society is that by acquiring knowledge, skills and abilities, students develop their cognitive, physical, social and creative abilities, and at the same time learn and build attitudes, adopt values of the environment and the wider community. Тhey grow up. By discovering the world, children’s cognitive abilities are developed, basic concepts are formed and the foundations for a system of concepts in the field of nature, society and culture are gradually built. The value of music in society and its diverse effects on people can be very important factors in creating a cultural identity. Getting to know the folk creation at a younger school age through traditional folk games with singing, leads us directly to preserving the traditions of our people. From today’s point of view, it is clear that folk dances with the singing of our country had and still have an integrative social function, since they influence the nurturing of collective identity at different levels of the community, is a symbol of national unity and transmits tradition from generation to generation. The paper presents an example of the social function of traditional folk dance through poetic, melodic-rhythmic analysis of a song, then folk costume, folk dance and folk instruments, based on the presented views.